Review of salivary diagnostics - A current scenario - Sadaksharam Jayachandran (Wolters Kluwer Medknow Publications, 2020)
Human saliva is produced by the three major salivary glands (the parotid gland, submandibular gland, and sublingual glands) and minor salivary glands. It contains several hormones, antibodies, cytokines, proteins, enzymes, and antimicrobial constituents that act as biomarkers. It also contains variable amounts of gingival crevicular fluid (GCF), mucosal transudate, desquamated epithelial cells, bacteria, viruses, fungi, food debris, microorganisms, serum, and some blood derivatives. Saliva has simple collection methods (non-invasive), handling procedure, reliable sensitivity and specificity, good cooperation from patients, and the possibility to perform dynamic studies. Salivary analysis can determine various systemic diseases, metabolic disorders, and infections. Hence, it serves as a potential diagnostic and prognostic tool with widespread clinical and research applications in various fields of science and medicine.